Cold snare polypectomy with pull technique of flat colonic polyps up to 12 mm: a porcine model - Tribonias, George (Ann Gastroenterol, 2015)
BACKGROUND: Most colonoscopic complications are polypectomy-related and occur more frequently during the removal of numerous small polyps. Therefore, it is important to have the best polypectomy approach of small polyps. The aim of the present animal study was to investigate the effectiveness and safety of cold snare polypectomy (CSP) technique combined with light pull of the snare in order to peel the mucosal and upper submucosal layer, namely pull CSP (PCSP), for the removal of polyps sized up to 12 mm in porcine models. METHODS: We performed a series of polypectomies in the pig colon with a double-channel experimental gastroscope using PCSP technique. RESULTS: Thirty cases of “polyps” larger than 7 mm and up to 12 mm were treated using PCSP technique. No sign of perforation or bleeding was observed in all cases performed with PCSP. CONCLUSIONS: According to our preliminary results in this animal model, PCSP could be a safe and effective technique for flat colonic polyp removal up to 12 mm in size consistent with the basic polypectomy principles.